Analisis Perbandingan Teori Dan Praktek Sistem Multi Level Marketing Pada Bisnis Paytren Dalam Perspektif Syariah - Midisen, Kisanda (ITB AAS INDONESIA Surakarta, 2024)
This study aims to find out how the application of the Multi Level Marketing Business system is applied to paytren, whether the practice in the field is in accordance with established sharia. The research method used in this case is library research and field research, with a qualitative descriptive research approach that is deductive in nature. Researchers used sources such as books, theses, articles, and conducted interviews with paytren business users. This study also uses a normative and comparative approach. Based on the research results, it can be concluded that the paytren business that uses a multi-level marketing system that has been certified by sharia in practice has many deviations both by its customers and by the system itself. The implementation of Paytren's multi-level sharia marketing is carried out in an unfair way, that is, whoever has subordinates or partners will also receive bonuses when their partners transact without having to work. In practice, paytren contains elements of usury, gharar and dzulm.